THREE CIRCLES MODEL REVITALISASI LEMBAGA PENGELOLA ZAKAT - Yulinartati Yulinartati; Ahmad Roziq; Lely Ana Ferawati Ekaningsih (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This study aims to identify and analyze: (a) potential sources of zakat, infak, andsedekah in Jember Regency, (b) systems and methods of fundraising, anagement,and distribution conducted by institutions of zakat, infak, and sedekah, (c)accountability of zakat, infak, and sedekah institutions, (d) the usefulness ofsuch funds to the recipient of zakat, infak, and sedekah, and (e) create a modelof revitalization of management of zakat, infak, and sadaqah institutions. Type of research is survey research by applying descriptive qualitative method. The results of this study found that management needs to revitalize institutions of zakat, infak, and sedekah as described in the Three Circles Model.